Cross-border medical tourism of tourists in Thailand’s border provinces: A case study of Laotian tourists in Nongkhai and Udon Thani Patthaphon - Sukjai, Patthaphon; Srirak, Chainarong (Kasetsart Journal of Social Sciences, 2022)
The objectives of this research article were to study: (1) trends in medical tourism in Thailand; (2) medical tourism in border provinces (Laotians in Nongkhai and Udon Thani); and, (3) address issues related to medical tourism. 400 questionnaires were administered to Laotian tourists using health business services in Nongkhai and Udon. Independent variables included characteristics and six factors related to decision-making about using Thai services. Dependent variables were expectations and satisfaction. First Order Confirmatory Factor Analysis indicated that 3 significant factors influenced decision-making: marketing promotion, need and service quality and price. Implications in the area of medical tourism and directions for future research are discussed.